China's Path to Consumer-Based Growth : Reorienting Investment and Enhancing Efficiency - Lee, Il (IMF Working Papers; Working Paper ;, 2013)
This paper proposes a possible framework for identifying excessive investment. Based on this method, it finds evidence that some types of investment are becoming excessive in China, particularly in inland provinces. In these regions, private consumption has on average become more dependent on investment (rather than vice versa) and the impact is relatively short-lived, necessitating ever higher levels of investment to maintain economic activity. By contrast, private consumption has become more self-sustaining in coastal provinces, in large part because investment here tends to benefit household incomes more than corporates. If existing trends continue, valuable resources could be wasted at a time when China's ability to finance investment is facing increasing constraints due to dwindling land, labor, and government resources and becoming more reliant on liquidity expansion, with attendant risks of financial instability and asset bubbles. Thus, investment should not be indiscriminately directed toward urbanization or industrialization of Western regions but shifted toward sectors with greater and more lasting spillovers to household income and consumption. In this context, investment in agriculture and services is found to be superior to that in manufacturing and real estate. Financial reform would facilitate such a reorientation, helping China to enhance capital efficiency and keep growth buoyant even as aggregate investment is lowered to sustainable levels.